Comparative analysis of physical fitness of high school students with regulatory requirements - Makhmudov Ravshan (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article presents the results of experimental studies of physical fitness of graduates of secondary schools in Fergana and their comparative analysis with the regulatory requirements of the "State Standards for Physical Education", the requirements for physical fitness of pre-conscription youth health tests "Alpomish".